The effect of continuous positive airway pressure treatment on physical activity in patients with obstructive sleep apnoea: A randomised controlled trial. - West, S; Kohler, M; Nicoll, D; Stradling, JR (2009)
BACKGROUND: Continuous positive airway pressure (CPAP) improves daytime sleepiness in patients with obstructive sleep apnoea (OSA). The effect of CPAP on physical activity is unclear. We hypothesized that activity would increase after CPAP treatment. METHODS: A double blind, parallel, randomised, controlled trial using therapeutic and placebo CPAP was performed in men with newly diagnosed OSA (more than 10>4% SaO(2) dips/hour and Epworth Sleepiness Score [ESS] 9). Activity was measured by wrist actigraphy before and after three months of CPAP therapy. RESULTS: Thirty-six men completed 1 week of continuous actigraphy before and after therapeutic CPAP (n=16) or placebo CPAP (n=20). The two groups were well-matched at baseline, with no significant differences in mean age, body mass index, ESS and SaO(2) dips/hour. Mean (SD) ESS and modified maintenance of wakefulness test (OSLER) improved significantly after CPAP. ESS change in the therapeutic group was -6.1 (4.4), compared to placebo, -2.8 (5.0); difference between groups p=0.04; OSLER (minutes), therapeutic +10.4 (14.4), placebo -5.0 (12.0), p=0.003. There was no significant difference between groups in mean hourly activity levels for the seven days at baseline; activity levels did not significantly change in either group after CPAP [daytime activity (arbitrary units): therapeutic -13.9 (93.1) vs. placebo +8.3 (62.9), p=0.4]. There was no correlation between change in activity and CPAP use. CONCLUSION: Activity does not increase after CPAP in men with OSA, despite improvements in daytime sleepiness. The reasons for this are not clear, but may be due to longstanding, habitual patterns of activity.